Recria de bovinos de corte e produção da pastagem de estrela africana sobressemeada com gramíneas e leguminosa com e sem uso de irrigação - Cavazzana, Jefferson Felipe (2019)
The need to increase the productivity of beef cattle in periods of low rainfall and reduce costs with nitrogen fertilization makes up the assumption of this research. Thus, the objective of this work was to evaluate the influence of the use of irrigation and the inclusion of forage legumes in grass-pasture-based on forage production, performance and animal ingestion behavior. The experimental design was completely randomized with four treatments (exclusive grasses, grasses + legumes, exclusive grasses + irrigation, grasses + legumes + irrigation), with three replications. The experiment was conducted from July 2017 to April 2018, at the Experimental Bovinoculture Unit of the Federal Technological University of Paraná, Southwest region of Paraná, Brazil. Twelve pickets with an average area of 3,000 m² were subdivided into four 750 m2 for use of the rotational stocking system. Twenty-four animal testers were used, castrated Angus-Nelore mid-calves with an initial mean weight of 240 kg. In the pasture, the accumulation rate, total yield, botanical composition and nutritive value were evaluated. The performance of the animals was evaluated by the average daily gain, animal load and ingestive behavior. Forage production and accumulation rate were higher with irrigation during winter and spring. In the spring, the irrigated grass and legume mixture obtained 39,8% higher yield than the exclusive grass, an increase of 2330 kg DM ha-1. Irrigated production attenuated the effects of low amount of forage observed in the absence of irrigation, and ryegrass and legumes were more productive in winter and spring. Irrigation provided a 9,7% increase in total forage production. In winter, crude protein content and “in vitro” dry matter digestibility were higher under irrigation and intercropping with legumes. Irrigation and intercropping with legumes resulted in an increase of 17,19% and 8,68% in animal unit per hectare, respectively. There were no differences in the ingestive behavior of the animals during the evaluation.